The effect of lower limb wearable resistance location on sprint running step kinematics - Feser, E.; Macadam, P.; Nagahara, R.; Cronin, J. (ISBS Proceedings Archive (Michigan), 2018)
This study quantified changes in step kinematics between unloaded, thigh, and shank wearable resistance (WR) at 2% body mass (BM) during over ground sprint running. Eleven male athletes completed two maximal effort sprint trials over 52 m of in-ground force plates, for each condition. There were no significant (p > 0.05) changes in sprint times between all conditions. Compared to unloaded sprinting, shank WR significantly changed step frequency (SF) (-2.1% acceleration phase and -2.5% max velocity phase (MVP)), contact times (CT) (2.1% MVP) and flight times (3.3% MVP); thigh WR significantly changed SF (-1.4% MVP) and CT (2.9% MVP). It appears peripheral loading (2% BM) of the thigh and shank affects SF and CT but not step length and width. Such differential loading could be used to train different mechanical determinants of speed.